ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PERBAIKAN JALAN PADA PEMERINTAH DAERAH KABUPATEN BATANG HARI DENGEN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Kurniawan, Irwan; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2019)
The road is an infrastructure that plays an important role in people's daily lives. Therefore, it is necessary to maintain and repair road conditions regularly. The existence of budget constraints causes not all damaged road sections can be handled. So that in handling road repairs it is necessary to determine priorities. In determining the priority of road improvement there are criteria that are taken into consideration in decision making. One method of analysis that can be used to overcome complexity due to various criteria is the Analytical Hierarchy Process (AHP) method. The AHP method is used to obtain the weight of 4 criteria that are taken into consideration in determining the priority of road improvement, namely road conditions, traffic volume, costs, and road classification. Calculation of scores for each road improvement proposal is obtained by multiplying the priority weight of the criteria by the criteria value of each proposal. The results show that the Decision Support System that is designed can produce a ranking of alternatives in the form of road improvement proposals based on predetermined criteria, so that it can be used as a basis for decision making to determine road improvement priorities.